Simultaneous targeting of TGF-β/PD-L1 synergizes with radiotherapy by reprogramming the tumor microenvironment to overcome immune evasion - Lan, Yan; Moustafa, Mahmoud; Knoll, Maximilian; Xu, Chunxiao; Furkel, Jennifer; Lazorchak, Adam; Yeung, Tsz-Lun; Hasheminasab, Sayed-Mohammad; Jenkins, Molly H.; Meister, Sarah; Yu, Huakui; Schlegel, Julian; et al. (Cancer cell, 2021)
Localized radiotherapy (RT) induces an immunogenic antitumor response that is in part counterbalanced by activation of immune evasive and tissue remodeling processes, e.g., via upregulation of programmed cell death-ligand 1 (PD-L1) and transforming growth factor β (TGF-β). We report that a bifunctional fusion protein that simultaneously inhibits TGF-β and PD-L1, bintrafusp alfa (BA), effectively synergizes with radiotherapy, leading to superior survival in multiple therapy-resistant murine tumor models with poor immune infiltration. The BA + RT (BART) combination increases tumor-infiltrating leukocytes, reprograms the tumor microenvironment, and attenuates RT-induced fibrosis, leading to reconstitution of tumor immunity and regression of spontaneous lung metastases. Consistently, the beneficial effects of BART are in part reversed by depletion of cytotoxic CD8+ T cells. Intriguingly, targeting of the TGF-β trap to PD-L1+ endothelium and the M2/lipofibroblast-like cell compartment by BA attenuated late-stage RT-induced lung fibrosis. Together, the results suggest that the BART combination has the potential to eradicate therapy-resistant tumors while sparing normal tissue, further supporting its clinical translation.